Critical Discourse Analysis of Megawati Soekarno Putri’s Amicus Curiae Letter for MK trial of Presidential Election Disputes - Diliana, Ekfindar; Nova Lina Sari Haheahan; Tobias Nggaruaka; Ricardo Goncalves Klau (Nusantara Journal of Multidisciplinary Science, 2024)
This study analyzes Megawati’s Amicus Curiae letter using discourse analysis, focusing on the construction of in-groups and out-groups, representation of social actors, and discursive strategies. The data analysis method involves Critical Discourse Analysis (CDA), focusing on how Megawati’s letter constructs in-group and out-group identities, represents social actors positively or negatively, and employs discursive strategies to legitimize in-group actions while criticizing the out-group. This approach utilizes frameworks from Van Dijk, Van Leeuwen, and Wodak to explore linguistic devices that shape audience perceptions. The findings revealed that the letter constructs the in-group as morally superior and aligned with justice, while the out-group is implied to be responsible for undermining democracy. Discursive strategies, such as moral appeals, historical references, and passive voice, are employed to legitimize in-group actions and subtly criticize the out-group. Additionally, Megawati's motives are highlighted as an effort to assert her political identity, position herself as a defender of democratic values, and enhance her influence in a competitive political landscape.